Do wage increases help? Wage increases and material hardships among low-wage hospital workers. Issue 2 (17th February 2023) - Woo, Jihee; Shook, Jeffrey; Goodkind, Sara; Ballentine, Kess; Engel, Rafael; Kim, Soobin; Petracchi, Helen
ABSTRACT: This study examines whether and how wage increases are associated with hardships experienced by low-wage workers and their strategies to manage these hardships. Data are drawn from a survey of 166 hospital service, clerical, and technical workers at a large hospital in Southwestern Pennsylvania. Following an initial wage increase, workers experienced fewer hardships and used fewer strategies to make ends meet, such as financial support from family and public benefits programs. Hardships decreased more for workers making above $15 an hour. These results suggest that raising the wages of low-wage workers can help reduce the hardships they experience and the need to use a variety of strategies to make ends meet.